Derivational and Semantic Characteristics of Zoonymous Onomatopoeia in Serbian - Štasni, Gordana R.; Štrbac, Gordana R. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper discusses the derivational and semantic characteristics of zoonymous onomatopoeia, based on the imitation of animal sounds. According to their morphological and communicative features, these units are primarily interjections. Nevertheless, from other onomatopoeic words, zoonymous onomatopoeias stand out for their productivity and semantic and derivational characteristics. The methodology applied in the work includes the usual procedures for semantic-derivative research — analysis of the formation structure of derivatives and the application of elements of componential analysis in the interpretation of the semantic extension of the observed units.Derivative analysis shows that most of these units have the inductive ability to create derivatives. In some cases, the derivation is blocked, which can be conditioned by different causes. Motive onomatopoeic interjections form nests of similar content. The most productive is the formation of verbs, which take on an inductive function and form a whole series of new derivatives.On the semantic level, zoonymous onomatopoeias are mostly one-meaning words, but their derivatives, verbs and nouns, are characterized by polysemy, the basis of which is most often a metaphorical transposition from the animal to the human as a designate, which is often accompanied by negative expressiveness, which goes in the derogatory direction, although there are other examples by positive expressiveness.
Keywords: zoonymous onomatopoeia; semantic-derivational potential; blocking; derivational direction; Serbian